Scat Singing Learning Method in Jazz Vocals for Vocal Students of Music Presentation Institut Seni Indonesia Yogyakarta - Agnes Tika Setiarini (Universitas Negeri Medan, 2023)
Scat singing is the designation of vocal improvisation techniques in jazz music. This form of vocal improvisation was first popularized by Louis Armstrong in 1962. Scat singing is often learned by imitating improvised musical instruments into vocals, such as saxophones, trumpets, guitars, or pianos. Popjazz vocal students of the ISI Yogyakarta Music Presentation study program began to be introduced and learned scat singing from semester 2 to semester 6. Only a few students successfully apply this vocal improvisation technique when singing in performances and jam sessions. The author as a lecturer of popjazz vocal practice in the Music Presentation Study Program has observed the difficulties experienced by the majority of students. Several stages of learning have been applied in the learning process, for example by understanding scales and chord patterns, developing the main melody in songs, enriching vocal dialects, to multiplying musical references. This stage of learning was not significantly successful in helping students master scat singing. This study aims to formulate a learning method of vocal improvisation techniques for scat singing. The data collection process is carried out by observing the learning process during lectures, interviews with students, and regular singing practice. Inductive qualitative data analysis, which is an analysis based on the data obtained then developed a certain relationship pattern or hypothesis. The research was conducted by qualitative methods, with the final result being a descriptive sentence formulation of steps to master the vocal improvisation technique of scat singing. This conclusion is expected to be an overview for lecturers in order to determine the right approach to help students master scat singing and dare to apply it in songs.